Prohibitions in criminal law - Serpak, Oleh (Problems of legality, 2024)
The article is devoted to the analysis of prohibitions in criminal law (criminal law prohibitions). Despite the fact that the issue of criminal law prohibitions is becoming increasingly relevant, it still remains poorly researched and controversial. This paper lays down the methodological foundations for the study of prohibitions in criminal law. In particular: 1) the author distinguishes between the concepts of «criminal law», «criminal legislation» and «criminal code»; 2) the author examines national criminal law through the prism of the public law branch of Ukraine (analyses certain aspects of criminal law regulation and criminal law relations; expresses the author’s position regarding the powers of entities representing the State in criminal law relations) 3) the author defines the concept of «criminal law provision», identifies its features, studies its structure, and also identifies the criteria for its classification. Taking into account the conclusions on the above issues, the author analyses prohibitions in the criminal law of Ukraine: the author proposes a definition of this term, identifies its features, makes its classification, and studies the legal consequences of violation of domestic criminal law prohibitions. The scientific work also contains the results of a study of foreign experience. Thus, the criminal legislation of the former USSR republics was subjected to a thorough study. The author notes that there are two models of understanding the concept of «prohibition in criminal law». In writing this article, the author used scientific works of Ukrainian and foreign legal scholars, as well as domestic and foreign regulatory legal acts. For a more detailed understanding of the subject matter of the study, the article is illustrated with three author’s diagrams and one map. The research work is a multidimensional analysis of prohibitions in criminal law, which allows for further development of this topic.